2015
DOI: 10.9734/indj/2015/17983
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Attachment. Family Interactive Dynamics and Psychopathology: What kind of Relationship in Adolescence?

Abstract: Introduction: This work is an example of empirical research. The aim was to look to the possible transgenerational influence between parents and adolescents attachment bond to their respective parents, infant armonic and/or disarmonic development and functional or dysfunctional family interactions. Methodology: 40 families with adolescents aged from 12 to 18 years (μ = 14.575, σ = 1.716) coming for a psychodiagnostic evaluation were tested with Lausanne Trilogue Play, Parental Bonding Instrument, Child Behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Secondly, we know from a general qualitative study that the families belonging to the subgroup studied in this work showed particular clinical peculiarities (Gatta et al, 2015a(Gatta et al, , 2015b(Gatta et al, , 2015c. Analyzing the peculiarities of these families we have observed that families with no parental support present at the time of the take in charge better parental competences and lower level of adolescent psychopathology.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Secondly, we know from a general qualitative study that the families belonging to the subgroup studied in this work showed particular clinical peculiarities (Gatta et al, 2015a(Gatta et al, , 2015b(Gatta et al, , 2015c. Analyzing the peculiarities of these families we have observed that families with no parental support present at the time of the take in charge better parental competences and lower level of adolescent psychopathology.…”
Section: Discussionmentioning
confidence: 79%
“…The main goal of this project was to assess the value of the Lausanne Trilogue Play paradigm (LTP; Fivaz-Depeursinge & Corboz-Warnery, 1999) in the diagnostic workup and treatment of families with children or adolescents revealing individual and/or familiar psychological problems Gatta et al, 2015aGatta et al, , 2015c.…”
Section: Introductionmentioning
confidence: 99%
“…A different perception of skills, emotional, and behavioral issues as reported in behavior-rating scales by different subjects (mother, father, and patient) is highlighted both in the present study and in national and international literature [72][73][74][75]. The different perception of psychological-psychiatric difficulties by different family members could be due to the stigma that is still attached to such pathologies, to potential feelings of guilt, to misinformation, and/or to the trivialization of psychological distress in children [7].…”
Section: Discussionmentioning
confidence: 98%